A Functional and Evolutionary Perspective on Transcription Factor Binding in Arabidopsis thaliana . Issue 10 (31st October 2014) - Heyndrickx, Ken S.; de Velde, Jan Van; Wang, Congmao; Weigel, Detlef; Vandepoele, Klaas
Abstract : An integrative meta-analysis of 27 transcription factor profiling experiments containing 15, 188 potential target genes in Arabidopsis is used to examine the organization and mechanisms underlying transcription factor regulation on a genome-wide scale. Binding complexity is related to type of the target gene, its function, and expression breadth but does not affect evolvability of the bound regions. Abstract: Understanding the mechanisms underlying gene regulation is paramount to comprehend the translation from genotype to phenotype. The two are connected by gene expression, and it is generally thought that variation in transcription factor (TF ) function is an important determinant of phenotypic evolution. We analyzed publicly available genome-wide chromatin immunoprecipitation experiments for 27 TFs in Arabidopsis thaliana and constructed an experimental network containing 46, 619 regulatory interactions and 15, 188 target genes. We identified hub targets and highly occupied target (HOT ) regions, which are enriched for genes involved in development, stimulus responses, signaling, and gene regulatory processes in the currently profiled network. We provide several lines of evidence that TF binding at plant HOT regions is functional, in contrast to that in animals, and not merely the result of accessible chromatin. HOT regions harbor specific DNA motifs, are enriched for differentially expressed genes, and are often conserved across crucifers and dicots, even though they are not under higher levels of purifying selection than non-HOT regions. Distal bound regions are under purifying selection as well and are enriched for a chromatin state showing regulation by the Polycomb repressive complex. Gene expression complexity is positively correlated with the total number of bound TFs, revealing insights in the regulatory code for genes with different expression breadths. The integration of noncanonical and canonical DNA motif information yields new hypotheses on cobinding and tethering between specific TFs involved in flowering and light regulation.